The value of student scientific society at the Department of Histology, Cytology and Embryology in clinical professional orientation. - Evtushenko, V. M. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Histology with embryology and cytology are core of basic medical and biological sciences, allowing us to formulate a better understanding of the principle of multi-level structure of the human body and hierarchical relationships within it, as well as the mechanisms of interaction of the human body with the environment in the norm and pathology. Objective. The aim of this study was to determine the effect of training students in the Student Scientific Society at the Department of Histology, Cytology and Embryology in their clinical career guidance. Results. Student Scientific Society allows us to provide not only the continuity of knowledge, but also the ability to use the available information, wider use of logical thinking. Taken together these possibilities create prerequisites for the formation of a mature clinical thinking. In-depth study of histology, cytology and embryology forms the basis for a better understanding of such fundamental disciplines as pathological anatomy, pathological physiology, pharmacology, that all together will be the basis for the clinical disciplines. Knowledge of histology, cytology and embryology is becoming increasingly important for the modern physician in terms of understanding the new diagnostic techniques, new technologies. The research work of the members of Student Scientific Society of Department of Histology, Cytology and Embryology contributes to more efficient practical skills. Conclusion. Student Scientific Society provides skills of independent work with scientific literature and ability to analyze and synthesize the material giving the basis for critical clinical data analyzes.